2019
DOI: 10.3390/antiox8100443
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid-Enriched Plant-Extract-Loaded Emulsion: A Novel Phytocosmetic Sunscreen Formulation with Antioxidant Properties

Abstract: The aim of this study was to develop a phytocosmetic sunscreen emulsion with antioxidant effect, containing a blend of flavonoid-enriched plant extracts. In vitro sun protection factor, antioxidant activity, skin irritation, photostability, cutaneous permeation, and retention of flavonoids were evaluated. Thermodynamically stable emulsions were obtained and tested for sensorial analysis after loading the blend of extracts. The selected emulsion was stable when stored at low temperatures (5 °C), for which after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 69 publications
1
47
0
3
Order By: Relevance
“…A red variety of Brazilian propolis has been described in the last years, with the ethanolic extracts being enriched in isoflavones, mainly formononetin, daidzein, and biochanin A [7]. Studies have demonstrated that such hydroalcoholic and ethanolic extracts have potential antitumoral activity both in vitro [8,9] and in vivo [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A red variety of Brazilian propolis has been described in the last years, with the ethanolic extracts being enriched in isoflavones, mainly formononetin, daidzein, and biochanin A [7]. Studies have demonstrated that such hydroalcoholic and ethanolic extracts have potential antitumoral activity both in vitro [8,9] and in vivo [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant activity of phenolic compounds such as flavonoids is widely known, and thus, flavonoids are widely studied as ingredients in cosmetic formulations against early skin aging by scavenging reactive oxygen species produced by sun radiation [4,22,51].…”
Section: Resultsmentioning
confidence: 99%
“…Continuing efforts in finding new sunscreens from natural products [22,23,24,25], the present study aimed at evaluating extracts of Dimorphandra mollis Benth, Ginkgo biloba L., Ruta graveolens L., and Vitis vinifera L., alone and as a mixture, as sunscreen filters using in vitro models.…”
Section: Introductionmentioning
confidence: 99%
“…The loading of active pharmaceutical ingredients (APIs) within nano-sized drug delivery systems is being currently exploited to promote product innovation by developing nanoproducts. Nanoproducts used for the delivery of APIs to the skin (e.g., nanopharmaceuticals, nanocosmeceuticals) have already proven their efficacy as several products are already available on the market for the treatment of skin injuries (e.g., atopic dermatitis [2], skin cancer [3], skin burns [4], wound healing [4,5]), and protection from ultraviolet (UV) radiations [6][7][8][9][10]. Some examples of daily contact with nanomaterials are given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%